Obesity, hypertension, and tobacco use associated with left ventricular remodeling and hypertrophy in South African women: Birth to Twenty Plus Cohort - Andrea Kolkenbeck‑Ruh; Larske M. Soepnel; Simone H. Crouch; Sanushka Naidoo; Wayne Smith; Shane A. Norris; Justine Davies; Lisa J. Ware (My University, 2022)
Background: Left ventricular hypertrophy (LVH) is a marker of increased risk in developing future life-threatening cardiovascular disease (CVD), however, it is unclear how CVD risk factors, such as obesity, blood pressure (BP), and tobacco use, are associated with left ventricular (LV) remodeling and LVH in urban African populations. Therefore, we aimed to identify the prevalence of LVH as well as the health factors associated with LV remodeling and LVH, within black South African adult women and their pre-pubescent children. Methods: Black female adults (n=123; age: 29–68 years) and their children (n=64; age: 4–10; 55% female) were recruited from the Birth to Twenty Plus Cohort in Soweto, South Africa. Tobacco and alcohol use, physical activity, presence of diabetes mellitus, heart disease, and medication were self-reported. Height, weight, and blood pressure were measured in triplicate to determine the prevalence of obesity and hypertension respectively. Echocardiogra‑ phy was used to assess LV mass at end-diastole, based on linear measurements, and indexed to body surface area to determine LVH. Results: Hypertension and obesity prevalences were 35.8% and 59.3% for adults and 45.3% and 6.3% for children. Self-reported tobacco use in adults was 22.8%. LVH prevalence was 35.8% in adults (75% eccentric: 25% concentric), and 6.3% in children. Concentric remodeling was observed in 15.4% of adults, however, concentric remodeling was only found in one child. In adults, obesity [OR: 2.54 (1.07–6.02; p=0.02)] and hypertension [3.39 (1.08–10.62; p=0.04)] signifcantly increased the odds of LVH, specifcally eccentric LVH, while concentric LVH was associated with selfreported tobacco use [OR: 4.58 (1.18–17.73; p=0.03)]. Although no logistic regression was run within children, of the four children LVH, three had elevated blood pressure and the child with normal blood pressure was overweight. Conclusions: The association between obesity, hypertension, tobacco use, and LVH in adults, and the 6% prevalence of LVH in children, calls for stronger public health eforts to control risk factors and monitor children who are at risk.
Keywords: Left ventricular hypertrophy, Ventricular remodeling, Sub-Saharan Africa, South Africa, Child health, Women’s health